Prevention of fraud with good corporate governance and internal control - Ely Suhayati; Ari Bramasto; Dedi Sarifudin; Nafisah Rahmania (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to determine how much good corporate governance and internal control can prevent fraud in SOES at Java island, with a sample of 15 representatives of SOES’s Internal Auditors in Java, while the method used in this study is descriptive and verification method using multiple regression and correlation analysis. The results of this study provide empirical evidence that the application of the principles of good corporate governance in SOES can prevent fraud, as well as an effective internal control can prevent fraud, this study concludes that if Good Corporate Governance and Internal Control are implemented properly, it can minimize fraud. Good Corporate Governance and Internal Control are consistently important to be implemented in all countries, to break the stigma from society towards SOES that have not been able to fully prevent fraud because they are not implemented strictly and consistently.